2013
DOI: 10.1259/dmfr.20120313
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a photostimulable storage phosphor digital system with or without the sharpen filter and cone beam CT for detecting approximal enamel subsurface demineralization

Abstract: Objectives: The aim of this study was to assess the performance of photostimulable storage phosphor (PSP) radiographs with or without using the sharpen filter and cone beam CT (CBCT) for detecting enamel subsurface demineralization. Methods: Enamel subsurface demineralization was induced on one of the approximal surfaces of 120 sound human teeth. Standardized images of all teeth were acquired after the demineralization phase using the Digora ® Optime (Orion Corp./Soredex, Helsinki, Finland) (PSP) and the i-CAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 34 publications
1
7
1
Order By: Relevance
“…Some studies evaluated the diagnosis of dental caries using CBCT images and found equivalent diagnostic performance to conventional and digital radiography. 8 9 12 18 19 However, the results obtained with CBCT in the present study disagree with those findings. Most previous studies validated CBCT using only teeth that were free of restorative materials (generally healthy teeth or teeth with small cavities or caries), unlike the present study.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Some studies evaluated the diagnosis of dental caries using CBCT images and found equivalent diagnostic performance to conventional and digital radiography. 8 9 12 18 19 However, the results obtained with CBCT in the present study disagree with those findings. Most previous studies validated CBCT using only teeth that were free of restorative materials (generally healthy teeth or teeth with small cavities or caries), unlike the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…The results obtained in the present study are in agreement with those of previous studies regarding intraoral radiographs. 8 9 12 18 Although the intraoral methods that those authors used differed from the method used in the present study, it can be said that, in vitro, the results of periapical radiography were the same as the results of the bitewing radiographs used in the present study. More specifically, the principle of image generation is the same; that is, the image detector and the objects are parallel to each other, and the central radiation beam is perpendicular to them.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…reported that use of “sharpen” filter resulted in high percentage of accurate detection of the presence (83%) and absence (79%) of enamel subsurface demineralization. [ 21 ] Abesi et al . and Castro et al .…”
Section: Discussionmentioning
confidence: 99%
“…A buffer solution, developed in previous studies for simulation of carious lesions (ten Cate, Duijsters, 1982;Argenta et al, 2003;Ferreira et al, 2007;Belém et al, 2013), final volume of 1500 ml, distilled and deionized water was added, and the pH was then set at 4.8. Approximately 1 g of thymol crystals was also added to avoid fungal growth.…”
Section: Demineralizing Inductionmentioning
confidence: 99%